2003
DOI: 10.1253/circj.67.35
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intraaortic Balloon Pumping on Left Ventricular Function in Patients With Persistent ST Segment Elevation After Revascularization for Acute Myocardial Infarction.

Abstract: n acute myocardial infarction (AMI), early, complete and sustained restoration of blood flow in the occluded coronary artery can salvage myocardium at risk and improve survival. 1 Revascularization of the occluded coronary artery with balloon angioplasty can be achieved in >90% of patients. 2 However, even early restoration of thrombolysis-in-myocardial-infarction (TIMI) grade 3 flow is not always associated with myocardial reperfusion because of microvascular damage. [3][4][5][6][7] Recent studies have demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Kurisu et al reported that IABP was effective in patients with persistent ST elevation after PCI for AMI. 40 …”
Section: Discussionmentioning
confidence: 99%
“…Kurisu et al reported that IABP was effective in patients with persistent ST elevation after PCI for AMI. 40 …”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, it is known that the salutary effect of β-blockers is greatest in high-risk patients. Patients with anterior AMI and RBBB should be recognized early and receive prompt and aggressive treatment such as β-blockers [25] or intraaortic balloon pumping [26].…”
Section: Rbbb In the Coronary Intervention Eramentioning
confidence: 99%
“…Because we could not perform myocardial contrast echocardiography routinely, a precise correlation between initial ST-segment magnitude and the no-reflow phenomenon remains unclear. However, this study indicates the need for adjunctive pharmacological [19][20][21][22] or mechanical therapy 23 to improve myocardial perfusion, especially in patients with total occlusion and ∑ST ≥10 mm. In addition, in patients with ∑ST <10 mm, reperfusion therapy increased ∑ST slightly but significantly.…”
Section: Present Studymentioning
confidence: 83%